Effects of the Asian Economic Crisis (AEC) on the MNEs in the ASEAN manaufacturing sector. - Gay, Serene Bee Koon. (2008)
The Asian Economic Crisis (AEC) had affected the Foreign Direct Investments (FDI) into ASEAN. This report analyze the effects of AEC on the FDI in the manufacturing sector by conducting primary and secondary research. This report also analyze the factors contributing to FDI, and avenues for future research.